Research on Paradox in Strategic Management: a Bibliometric Analysis from 2000 to 2021 - Thoha, Ahmad Faiz Khudlari (Journal of Business & Banking, 2022)
The sustainability of strategic management processes demands the accommodation of different expectations. The idea of paradox encourages organizational leaders to manage conflicts by accommodating the competing impulses. In the past quarter century, the theory of paradox and its continuous evolution has evolved dramatically, presenting excellent opportunities amid the speed of technological progress, reduced resources, and diverse customer expectations. The study comprehensively analyzes paradoxical concepts in current strategic management research and explores future related literature development opportunities. The bibliometric analysis method was used in this study to map and evaluate trends of paradox in strategic management domains using a statistical approach to 633 articles from Scopus. The results show that paradox in strategic management has implications related to servitization, open innovation, organizational change, ambidexterity, knowledge sharing, diversity, value creation, corporate sustainability, dynamic capabilities, and social entrepreneurship. The results of this study can guide the researchers to develop paradoxical research in the field of strategic management in the future.